2018
DOI: 10.1177/1120672117753701
|View full text |Cite
|
Sign up to set email alerts
|

Single long scleral tunnel technique for prevention of Ahmed valve tube exposure

Abstract: Single long scleral technique was efficacious with no occurrence of tube exposure in relatively long period of follow-up. In this method, there is no need to harvest any additional material, and in situations with limited access to patch grafts, it is performable with the minimal facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
0
15
2
1
Order By: Relevance
“…6 Intrascleral tunnel techniques for AGV implantation have been previously described. [6][7][8][9][10][11][12][13] However, to our knowledge, the creation of a long intrascleral tunnel using a 23 G needle for AGV implantation in a cohort of vitrectomized eyes only, along with the related physical deductions and explanations, are new to the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Intrascleral tunnel techniques for AGV implantation have been previously described. [6][7][8][9][10][11][12][13] However, to our knowledge, the creation of a long intrascleral tunnel using a 23 G needle for AGV implantation in a cohort of vitrectomized eyes only, along with the related physical deductions and explanations, are new to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These include the realization of a scleral tunnel with a crescent knife or with a 23 G needle, and insertion of the valve tube in the AC through the tunnel. [6][7][8][9][10][11][12][13] Advantages of these techniques include a lower rate of valve tube exposure and postoperative hypotony complications, the absence of a covering patch with related aqueous leak, and being sutureless. However, there is a lack of reports describing the advantages of performing a 23 G needle tunnel in vitrectomized eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have been carried out with promising results with many reporting no tube exposure during the reported follow-up period (from 6 months to about 10 years). [42][43][44][45][46][47][48] Kugu et al found the rate of tube exposure in patients who underwent surgery by long scleral tunnel technique to be significantly lower than those who underwent implantation by processed pericardium patch graft method alone, 2.5% (1 of 40 eyes) and 7.9% (3 of 38 eyes), respectively, over a mean follow-up duration of 46.7 ± 19.4 months. 49 In a study by Ollila et al comparing 332 eyes with simple scleral flap coverage and 92 eyes who had the addition of a 6-7 mm long scleral tunnel posterior to the scleral flap, erosion rate was 4.5% in the group with simple scleral flap (median follow-up 3.5 months [1-72 months]) while the other group had no erosions (median follow-up 22 months [10-39 months]) (p = 0.042).…”
Section: Methods Of Tube Coveragementioning
confidence: 99%
“…These techniques may be especially useful in countries that do not have access to patch grafts. Multiple studies have been carried out with promising results with many reporting no tube exposure during the reported follow‐up period (from 6 months to about 10 years) 42–48 . Kugu et al found the rate of tube exposure in patients who underwent surgery by long scleral tunnel technique to be significantly lower than those who underwent implantation by processed pericardium patch graft method alone, 2.5% (1 of 40 eyes) and 7.9% (3 of 38 eyes), respectively, over a mean follow‐up duration of 46.7 ± 19.4 months 49 .…”
Section: Risk Factors For Implant Exposurementioning
confidence: 99%
“…2,14 Scleral tunnels have just been proposed to prevent tube erosion in primary tube surgery even if the tube was inserted into anterior chamber via a scleral flap. 15,16…”
Section: Introductionmentioning
confidence: 99%